Mimesis and cultural-psychological foundations of conflict - Ekadumov, Andrew I. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
Cross-cultural interaction is carried out in accordance with a two-level structure of communication. The dialogue of physically autonomous communicators is conducted within the autodialogical process, in the structure of figurative-symbolic notions of the communicating individuals. In the absence of interpersonal dialogue, but when the Other is being observed, the cross-cultural dialogue is initiated at the auto-communicative, intrapersonal level. Outside of interpersonal communication, conflict over unacceptable cultural strategies can be triggered by their effect on the recipient’s symbolic notions only due to observation of alien cultural manifestations.
Keywords: mimesis; communication; auto-communication; mimetic wish; constitutional violence